2018
DOI: 10.1021/acs.jafc.8b05231
|View full text |Cite
|
Sign up to set email alerts
|

Preharvest Application of Elicitors to Monastrell Grapes: Impact on Wine Polysaccharide and Oligosaccharide Composition

Abstract: This work studied the effect of preharvest application in Monastrell grapes of four different elicitors [methyl jasmonate (MeJ), benzothiadiazole (BTH), chitosan from fungi (CHSf), and chitosan from seafood (CHSs)] on wine polysaccharide and oligosaccharide fractions. The polysaccharide and oligosaccharide fractions were isolated and characterized. Neutral monosaccharides were released after hydrolysis of polysaccharides and quantified by gas chromatography (GC). Sugar composition of oligosaccharides was deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 51 publications
4
11
0
Order By: Relevance
“…In contrast, Apolinar-Valiente et al (2018) concluded that the application of methyl jasmonate, benzothiadiazole, chitosan from fungi, and chitosan from seafood elicitors in the clusters of the vineyard of Monastrell grapes affected the extraction of monosaccharides in the wines. In the 2019 and 2020 wines, the major monosaccharides differed: in terms of glycosylated residues, galacturonic acid and mannose showed the second highest levels in the 2019 and 2020 wines respectively, and mannose and arabinose the third highest levels in the 2020 and 2019 wines respectively.…”
Section: Effect Of Elicitors On the Glycosyl Residue Composition Of G...mentioning
confidence: 93%
See 4 more Smart Citations
“…In contrast, Apolinar-Valiente et al (2018) concluded that the application of methyl jasmonate, benzothiadiazole, chitosan from fungi, and chitosan from seafood elicitors in the clusters of the vineyard of Monastrell grapes affected the extraction of monosaccharides in the wines. In the 2019 and 2020 wines, the major monosaccharides differed: in terms of glycosylated residues, galacturonic acid and mannose showed the second highest levels in the 2019 and 2020 wines respectively, and mannose and arabinose the third highest levels in the 2020 and 2019 wines respectively.…”
Section: Effect Of Elicitors On the Glycosyl Residue Composition Of G...mentioning
confidence: 93%
“…The polysaccharides from the skin cell walls probably contributed more to TMS content in 2019 wines than those from pulp. The cell walls of the skin are rich in polysaccharides, because the cells are smaller, more compact and have thicker walls than the cells of the pulp (Apolinar-Valiente et al, 2018). Other authors also point out that the extractability of polysaccharides increases with grape maturity (Gil et al, 2012;Martínez-Lapuente et al, 2016).…”
Section: Effect Of Elicitors On the Glycosyl Residue Composition Of G...mentioning
confidence: 99%
See 3 more Smart Citations